“Smartphone Migration”: Emerging Lifestyle and Changing Habits of Indian Labor Migrants in Johannesburg - Yengde, Suraj (Archīum Ateneo, 2014)
This paper aims to understand the life of Indian labor migrants in the post-migration phase. To understand the cultural aspects of labor migrants is to understand their everyday life activities. Migration for contemporary young migrants, which is the core interest of this paper, is about experiencing a new life in a new country, thinking about the present, and planning the future. Getting a job, starting a business, partnering with fellow Indian workers, or marrying a local South African—these encompass the idea of assimilation and adaptation. This paper looks at the cultural aspects of migration that drive labor migrants to South Africa, with a focus on the Indian business district in Johannesburg, Fordsburg, and the flea market area, which is a hub for South Asian businessmen and labor migrants.